A catalogue of the species of Mesostigmata (Arachnida, Acari, Parasitiformes) recorded from Ireland including information on their geographical distribution and habitats - Bolger, Thomas; Arroyo, Julio; Piotrowska, Katarzyna (Zootaxa, 2018)
The study of Irish Mesostigmata extends back for more than 100 years, and most of the principal Irish habitat types have been studied. In this paper we provide a catalogue of the species of Mesostigmata (Arachnida, Acari, Parasitiformes) recorded from Ireland over that time. The catalogue includes 329 species, information on the habitats and locations where they occurred and provides a comprehensive list of the literature related to the Irish fauna. This catalogue increases the number of Mesostigmata species known in Ireland by 40% over the number recorded in the most recent catalogue (Luxton, 1998).